Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture